Knowledge Priorities on Climate Change and Water in the Upper Indus Basin: A Horizon Scanning Exercise to Identify the Top 100 Research Questions in Social and Natural Sciences. Issue 4 (13th April 2022) - Orr, Andrew; Ahmad, Bashir; Alam, Undala; Appadurai, ArivudaiNambi; Bharucha, Zareen P.; Biemans, Hester; Bolch, Tobias; Chaulagain, Narayan P.; Dhaubanjar, Sanita; Dimri, A. P.; Dixon, Harry; Fowler, Hayley J.; et al.
Abstract: River systems originating from the Upper Indus Basin (UIB) are dominated by runoff from snow and glacier melt and summer monsoonal rainfall. These water resources are highly stressed as huge populations of people living in this region depend on them, including for agriculture, domestic use, and energy production. Projections suggest that the UIB region will be affected by considerable (yet poorly quantified) changes to the seasonality and composition of runoff in the future, which are likely to have considerable impacts on these supplies. Given how directly and indirectly communities and ecosystems are dependent on these resources and the growing pressure on them due to ever‐increasing demands, the impacts of climate change pose considerable adaptation challenges. The strong linkages between hydroclimate, cryosphere, water resources, and human activities within the UIB suggest that a multi‐ and inter‐disciplinary research approach integrating the social and natural/environmental sciences is critical for successful adaptation to ongoing and future hydrological and climate change. Here we use a horizon scanning technique to identify the Top 100 questions related to the most pressing knowledge gaps and research priorities in social and natural sciences on climate change and water in the UIB. These questions are on the margins of current thinking and investigation and are clustered into 14 themes, covering three overarching topics of "governance, policy, and sustainable solutions", "socioeconomic processes and livelihoods", and "integrated Earth System processes". Raising awareness of these cutting‐edge knowledge gaps and opportunities will hopefully encourage researchers, funding bodies, practitioners, and policy makers to address them. Plain Language Summary: Huge populations of people across Pakistan, India, China, and Afghanistan depend on river systems originating from the mountainous Upper Indus Basin (UIB) region. These river systems are fed by snow and glacier melt and rainfall. However, demand for freshwater is growing due to population growth, industrialization, urban development, etc, and climate change also poses a serious threat to the water supply. These two pressures pose considerable adaptation changes. The strong connections between water resources, climate change, and human activities within this region, therefore, suggest that a multi‐disciplinary research approach combining social and natural/environmental sciences is required for successful adaptation to ongoing and future climate change. Here we use a 'horizon scanning' technique to identify the Top 100 questions related to the most pressing knowledge gaps and research priorities in social and natural sciences on climate change and water in the UIB. Raising awareness of these cutting‐edge knowledge gaps and opportunities will hopefully encourage researchers, funding bodies, practitioners, and policy makers to address them and help inform future water management, climate plans, and development policy in the UIB. Key Points: The Top 100 research questions on climate change and water in the Upper Indus Basin in the social and natural sciences are identified Many questions are cross‐disciplinary given the strong linkages between climate, water, and human activities in the Upper Indus Basin Questions are identified using horizon scanning, which is a technique used to identify knowledge gaps relevant to emerging challenges